Application of Google Products/Services in LIS Profession (LIS TODAY, 2021)
The study tries to make awareness among the library and information science professionals to use  Google products/services for enhancing the library and information services at zero investment. The  paper reveals the products/services of Google which can be utilized in libraries and information  centers for efficient working. The paper also describes how librarians and library staff can use google  products/services for fulfilling various tasks and objectives of library and information centers. The  researcher has given several suggestions to library professionals regarding the use of google  products/services in library and information centers.
Keywords: Social networking; Google app; LIS Online Societies